Banana Xanthomonas Wilt disease management through roguing affects ground-dwelling arthropods composition, abundance and diversity - Tinzaara, William; Ocimati, Walter (EANSO, 2025)
The role of ground-dwelling arthropods in sustaining cropping systems by providing ecosystem services is well appreciated. This study was conducted to determine the effects of roguing of diseased banana plants as a banana Xanthomonas wilt (BXW) management practice on ground-dwelling arthropod composition, abundance and diversity in a banana cropping system. The study determined the composition, abundance and diversity of ground-dwelling arthropods in banana plots of different roguing levels during two seasons, and evaluated the seasonal effects on the diversity of species in the different plots of different roguing levels. Arthropods captured from plots of different roguing levels were assessed for richness, evenness and diversity index. The total number of arthropod families captured from different plots was generally similar. A total of 62, 64, 65 and 72 families were captured from plots of 0, 25, 50, and 100% roguing levels, respectively. The number of species captured in the four treatments was statistically similar, although they increased with the level of roguing. The Shannon diversity index was lowest for catches in 25% (0.029) and highest in 100% (1.28) rogued plots. The Shannon diversity index values were generally low, suggesting that few species were more abundant than others and that the different plots had low arthropod diversity. The arthropod diversity was generally similar to samples taken during the wet and dry seasons. This study provides evidence that the BXW disease control practices did not negatively impact the ground-dwelling arthropods' composition, abundance and diversity.